Influence of cricket powder content and placebo effect on consumers’ acceptance of sweet biscuits - Cabagnols, Solène (2025)
Introduction. Insect-based foods represent an emerging alternative to conventional food products. Insect powders are an important protein source with reduced ecological impact, though its incorporation into foods should consider effects on sensory properties and nutritional profiles. Objective. To assess consumer acceptance of sweet biscuits with cricket powder in Costa Rica, and evaluate the nutritional profiles of the products developed. Materials and methods. The study was conducted at the Universidad de Costa Rica, San José, Costa Rica in 2023. Sweet biscuits containing varying proportions of cricket powder (0.0, 12.5, and 26.0 %) were manufactured to evaluate both placebo effect and effect of cricket powder content influence on consumer acceptance, using two distinct panel groups. Demographic information, attitudes towards entomophagy, and perceived importance of protein consumption were collected via questionnaire. Proximate analysis and detailed fatty acid composition were performed on the three tested formulations with cricket powder. Results. Study populations demonstrated positive attitude towards insect consumption. The overall acceptance of the “No cricket” sample was significantly lower compared to both “Cricket” and “Commercial” samples. Biscuits containing 12.5% cricket powered achieved significantly higher overall sensory acceptance compared to the “26.0 % cricket powder” sample and showed no significant difference from the “Commercial” sample. Consumer segmentation was accomplished through Agglomerative Hierarchical Clustering. Primary nutritional differences between samples were observed in crude fat and specific fatty acids contents. Conclusions. Results indicate high consumer acceptance of sweet biscuits with cricket powder in Costa Rica. Nutritional analysis revealed progressive increases in crude fat and specific fatty acids contents corresponding to increased cricket powder incorporation.